PELACAKAN TITIK DAYA MAKSIMUM PHOTOVOLTAIC DC-DC BOOST CONVERTER DENGAN ALGORITMA P&O - Matalata, Hendi; Wustha Johar, Leily; Eka Yandra, Fadli (ITP Press, 2024)
Photovoltaic (PV) is an environmentally friendly renewable energy source. When Photovoltaics are connected directly to a load, the power delivered to the load is not optimal power. Therefore, it is important to get maximum power from the PV system thereby increasing efficiency. Various maximum power point tracking (MPPT) techniques of PV systems are proposed, such as Perturb and Observe (P&O) algorithm. MPPT techniques are usually limited to uniform weather conditions. This research presents an MPPT system with a series of DC-DC Boost converters under conditions of changes in solar irradiation, each change is assumed to last 5 hours and a temperature of around 250C, while the amount of solar irradiation is 300 W/m2, 500 W/m2, 700 W/m2 and 1000 W/m2. From the results of research carried out with the help of MATLAB simulations, it was found that the average efficiency was 95.6% and obtained low oscillation MPP tracking as well as fast and dynamic response during stable weather conditions.